The effectiveness of giving beetroot juice on increasing hemoglobin (hb) levels of adolescent women in islamic boarding school - Kartika Pibriyanti; Hurin Safira; Lulu' Luthfiya (University of Darussalam Gontor, 2021)
Background: About 50% of cases of anemia are due to iron deficiency, Southeast Asian State was in the 2nd highest position for anemia compared to other countries. The incidence of anemia is at greater risk in women due to natural conditions such as menstruation, pregnancy and childbirth as well as the food consumed. The prevalence of anemia in Indonesia is 21,7% with a proportion of 20,6% in urban areas and 22.8% in rural areas. Purpose: The purpose of this study was to determine the effectiveness of giving beetroot juice to increase hemoglobin levels in the blood in adolescents women in Islamic boarding school. Method: This research was conducted using a pre-experimental method with one group pretest post-test design. The intake of 60 g of beetroot is consumed in the form of 200 ml/day of beetroot juice for 7 days. Result: There is a significant difference hemoglobin levels before and after giving beetroot juice in adolescent women at Islamic boarding school (p=0.001). Conclution: Consumption of beetroot juice has an effect on increasing hemoglobin levels in adolescent women.